Increased RSV-A Bronchiolitis Severity in RSV-Infected Children Admitted to a Reference Center in Catalonia (Spain) Between 2014 and 2018. Issue 3 (6th February 2023) - Vila, Jorgina; Lera, Esther; Peremiquel-Trillas, Paula; Andrés, Cristina; Martínez, Laia; Barceló, Irene; Carsi, Ariadna; Balcells, Joan; Ángel Rodrigo-Pendás, José; Soler-Palacín, Pere; Rodrigo, Carlos; Antón, Andrés
Abstract: Between 2014 and 2018, we evaluated the severity of 687 cases of bronchiolitis caused by respiratory syncytial virus (RSV) in Catalonia, Spain. Compared to RSV-B, RSV-A cases required intensive care (adjusted relative risk (aRR) = 1.44, p < 0.01) and respiratory support (aRR = 1.07, p < 0.01) more often; hospital stay was one day longer ( p < 0.01). Subgroup identification may aid clinical evaluation and seasonal healthcare planning. Abstract : Respiratory syncytial virus A (RSV-A) bronchiolitis, compared with RSV-B, had greater severity at hospital admission, lengthier hospital and pediatric intensive care unit (PICU) length of stay, more proportion of PICU admissions, and higher respiratory support requirements. Both groups had similar demographic characteristics and similar rates of prematurity and comorbidities.